Developing an online facilities reservation system / Mohd Noor Ameen Mohd Surijo - Mohd Surijo, Mohd Noor Ameen (2006)
Online Facilities Reservation System (OFRS) is one of the E-Office modules for FTMSK. OFRS refers to entities that provide services for an individual to have access to FTMSK's facilities information via an electronic medium such as Internet, Intranet and direct connection. The facilities reservation module allows the individuals to hire out computer lab, lecture rooms, meeting rooms and/or other facilities. The development of OFRS can improve the efficiency and accuracy of room and equipment processes for FTMSK's academicians. This development used Open ACS web application framework as project development framework and Application Framework Development Process as project methodology. As a result. Online Facilities Reservation System (OFRS) has been developed.